Searching for Genetic Biomarkers for Hereditary Angioedema Due to C1-Inhibitor Deficiency (C1-INH-HAE) - Parsopoulou, Faidra; Loules, Gedeon; Zamanakou, Maria; Csuka, Dorottya; Szilagyi, Agnes; Kompoti, Maria; Porebski, Grzegorz; Psarros, Fotis; Magerl, Markus; Valerieva, Anna; Staevska, Maria; Obtulowicz, Krystyna; et al. (Frontiers in Allergy, 2022)
Existing evidence indicates that modifier genes could change the phenotypic outcome of the causal SERPING1 variant and thus explain the expression variability of hereditary angioedema due to C1-inhibitor deficiency (C1-INH-HAE). To further examine this hypothesis, we investigated the presence or absence of 18 functional variants of genes encoding proteins involved in the metabolism and function of bradykinin, the main mediator of C1-INH-HAE attacks, in relation to three distinct phenotypic traits of C1-INH-HAE patients, i.e. the age at disease onset, the need for long-term prophylaxis (LTP) and the severity of the disease. Genetic analyses were performed by a validated next-generation sequencing platform. Two hundred and thirty-three C1-INH-HAE patients from 144 unrelated families from five European countries were enrolled in the study. Already described correlations of five common functional variants [F12-rs1801020, KLKB1-rs3733402, CPN1-rs61751507 and two in SERPING1 (rs4926 and rs28362944)] with C1-INH-HAE severity were confirmed. Furthermore, significant correlations were detected between either the age at disease onset, the long-term prophylaxis or the severity score of the disease, and a series of other functional variants (F13B-rs6003, PLAU-rs2227564, SERPINA1-rs28929474, SERPINA1-rs17580, KLK1-rs5515, SERPINE1-rs6092, F2-rs1799963). Interestingly, correlations uncovered in the whole cohort of patients were different than those in the cohort of patients carrying missense causal SERPING1 variants. Our findings indicate that variants other than the SERPING1 causal variants act as independent modifiers of C1-INH-HAE severity and could be tested as possible prognostic biomarkers.